2014
DOI: 10.1038/ni.3028
|View full text |Cite
|
Sign up to set email alerts
|

A narrow repertoire of transcriptional modules responsive to pyogenic bacteria is impaired in patients carrying loss-of-function mutations in MYD88 or IRAK4

Abstract: Loss of function in the kinase IRAK-4 or the adapter MyD88 in humans interrupts a pathway critical for pathogen sensing and ignition of inflammation. Yet patients with loss of function mutations are surprisingly only susceptible to a limited range of pathogens. We employed a systems approach to investigate transcriptome responses following in vitro exposure of patients’ blood to Toll-like receptor and interleukin-1 receptor agonists, and whole pathogens. Responses to purified agonists were globally abolished b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 50 publications
2
91
0
1
Order By: Relevance
“…It seems intriguing that monocytes as circulating MF progenitors do not require TLR13 or UNC-93B and, hence, endosomal TLR signaling altogether, for a potent cytokine response to streptococci and staphylococci. In line with this data, a recent study of patients deficient in MyD88/IRAK4 demonstrated a residual responsiveness of blood cells to whole heat-killed bacteria, in contrast to the complete loss of response to purified bacterial TLR ligands (43). In this context, the discrete role of MyD88 in circulating myeloid cell subsets in response to GBS remains to be established.…”
Section: Discussionmentioning
confidence: 63%
“…It seems intriguing that monocytes as circulating MF progenitors do not require TLR13 or UNC-93B and, hence, endosomal TLR signaling altogether, for a potent cytokine response to streptococci and staphylococci. In line with this data, a recent study of patients deficient in MyD88/IRAK4 demonstrated a residual responsiveness of blood cells to whole heat-killed bacteria, in contrast to the complete loss of response to purified bacterial TLR ligands (43). In this context, the discrete role of MyD88 in circulating myeloid cell subsets in response to GBS remains to be established.…”
Section: Discussionmentioning
confidence: 63%
“…Chaussabel et al (Chaussabel et al, 2008) developed a strategy for blood microarray data analysis which identified genes co-expressed across multiple disease datasets and classified them into 28 blood transcriptional modules. The genes belonging to such functionally related clusters can be used to generate a disease-specific transcription signature which may serve for diagnostics or treatment prognosis (Berry et al, 2010). In another approach, 334 blood transcriptional modules (BTMs) were annotated according to biological function or tissue-specific expression by Li et al (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In order to generate feature sets based on gene co-expression, several studies have attempted to determine meaningful relationships between genes based on their regulation; by measuring changes in gene expression under various environmental conditions in distinct organisms they have provided models for the discovery of transcriptional modules (Bar-Joseph et al, 2003;Liu et al, 2007), resulting in a broad range of gene classification collections. Chaussabel et al (Chaussabel et al, 2008) developed a strategy for blood microarray data analysis which identified genes co-expressed across multiple disease datasets and classified them into 28 blood transcriptional modules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations